Implant impingement during internal rotation after reverse shoulder arthroplasty. The effect of implant configuration and scapula anatomy: A biomechanical study. (March 2016) - Krämer, Manuel; Bäunker, Alexandra; Wellmann, Mathias; Hurschler, Christof; Smith, Tomas
Abstract: Background: Internal rotation after reverse shoulder arthroplasty is essential to perform fundamental daily living activities. The purpose of this study was to examine the impact of anatomical and implant related factors on impingement-free internal rotation of the glenohumeral joint. Methods: CT-scans of 13 human shoulder specimens with implanted reverse shoulder prostheses were carried out and scapula neck length, lateral pillar angle, and implantation height of the metaglene were measured. Internal rotation testing of all specimens was performed by the use of a robot assisted shoulder simulator. Biomechanical variables were analyzed using a three-way ANOVA. Spearman's rank correlations were performed to determine the relationship between biomechanical and anatomical data. Findings: The maximum internal rotation angle for a 38 mm centric glenosphere and a standard onlay was 93.4(SD 34.9°). The change of the diameter of the glenosphere resulted in no significant increase of the maximum rotation angle ( P = 0.16), while change of the glenosphere type from concentric to eccentric ( P = 0.005) as well as the change of the onlay type from standard to a more shallow one ( P = 0.002) both had a significant effect on the internal rotation. The distance between the inferior rim of the metaglene and the inferior aspect of the glenoid ( P = 0.21), scapula pillar angle ( P = 0.13) as well as the scapula neck length ( P = 0.81) showed no significant correlation with the maximum internal rotation angle. Interpretation: Implant component selection shows strong influence on the impingement-free internal rotation. The use of an eccentric glenosphere and a shallow humeral cup may improve internal rotation after reverse shoulder arthroplasty. Highlights: No influence of scapular anatomy on maximum internal rotation Internal rotation can be improved biomechanically by the use of eccentric glenospheres. Internal rotation can be improved biomechanically by the use of shallow humeral cups. Improved internal rotation may reduce restrictions in daily living activities.